PERAN KEPALA SEKOLAH DALAM UPAYA MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI ERA PEMBELAJARAN ABAD 21 (Studi SMK Pusat Keunggulan Al-Azhar Menganti Gresik) - Sahrun Nizam, M.; Usman, Fadly (Menara Tebuireng, 2024)
Abstract— The biggest challenge in the 21st century learning era is how educators can face challenges and adapt to the development of this era. The success of students in learning is also influenced by the professional competence of teachers. Therefore, the role of the Principal is very important in efforts to improve the professional competence of teachers to survive in the current globalisation and advance the school they lead. This study aims to analyse and describe how the role of the Principal's strategy in improving the professional competence of teachers in the 21st century learning era as well as the supporting and inhibiting factors in improving the professional competence of teachers at SMK Pusat Excellence Al-Azhar Menganti. While the type of research used is descriptive qualitative research with a case study approach conducted at SMK Pusat Keunggulan Al-Azhar Menganti Gresik intensively, in detail and in depth about certain events and phenomena in order to obtain valid information. The results showed 1) The role of the Principal as a manager, (educator) educator, and as a motivator as a way to improve the professional competence of teachers; 2) The strategic role of the Principal is to provide training programmes, workshops, and in house training as an effort to digitally improve the professional competence of teachers in facing the demands and challenges of 21st century learning, assisting teachers in improving the quality of their performance and a means of integrating the curriculum applied in schools with the needs of the Industrial World; 3) Supporting factors are competent Human Resources (HR), strong teacher responsibility. Willingness to continue learning, and high motivation to create and innovate. While the inhibiting factors are the inability to manage personal problems, lack of time management skills, cost factors, location, family and limited infrastructure facilities. Keyword: Principal, Teacher Professional Competence, 21st Century Learning